Hank Krause letter to Thomas H. Kent regarding bird sightings, spring 1986 - Krause, Hanket al (1986)
Field notes contributed by Hank Krause in a letter to Thomas H. Kent. This item was submitted past the deadline for the Iowa Ornithologists Union Quarterly field report of spring 1986. Epson - sheet feed